EDUKASI DAN DETEKSI DINI PENYAKIT MELALUI GERAKAN MASYARAKAT HIDUP SEHAT (GERMAS) DI DSN SIMO II DS SIMO WILAYAH KERJA UPT PUSKESMAS KWADUNGAN KABUPATEN NGAWI - Prawoto, Edy; Nisak, Raudhotun; Hidayah, Nurul (Jurnal Pengabdian Kesehatan, 2024)
Change of lifestyle have led to an increase in various diseases, especially non-communicable diseases (NCDs). The increase in these diseases not only affects the health status of individuals, but also adds to the burden and financing of the state. The Healthy Living Community Movement (Germas) is one of the alternative solutions offered to reduce the prevalence of NCDs and other diseases that result from unhealthy lifestyles. The purpose of this community service activity is to conduct early detection of disease and educate residents to actively participate in the healthy living community movement. This activity was carried out on May 8 to June 2, 2023 in the Simo II Hamlet area, Simo Village, Kwadungan District, Ngawi Regency. The results of the implementation of this activity are that a small proportion of residents experience hypertension (23 people), Diabetes Mellitus (6 people), hyperuricemia (12 people), and hypercholesterolemia (8 people). The education that has been provided has also increased the knowledge of local residents where good knowledge is 75%, sufficient knowledge is 15%, and poor knowledge is 10%. This change in knowledge is expected to improve the behavior of the community to be active in Germas so that it can reduce the prevalence of diseases that arise due to unhealthy lifestyles in order to improve optimal health levels